Amplifying the Influence of CSR Disclosure on Investment Inefficiency by Choosing Woman Directors: Is it Effective? - Ulfah Tika Saputri; Fitri Agustina (Universitas Muhammadiyah Yogyakarta, Indonesia, 2022)
Research Aims: The article was written with the intention to inspect the amplified impact of CSR disclosure by choosing women on the boards of directors in the companies on investment inefficiency. Design/Methodology/Approach: The sample studies were non-financial companies listed on IDX during 2018-2019 that published sustainability and annual reporting.Research Finding: This research revealed that, in the latest two years, overinvestment was done by most of the sample companies (76%). Hereafter, there was a negative effect on investment inefficiency due to the increasing corporate social responsibility disclosure. Nevertheless, women on the board of directors had no effect as moderating variable.Theoretical Contribution: This study adds literature on investment inefficiency issues, especially on amplifying the influence of corporate social responsibility disclosure on investment inefficiency by choosing women on the board of directors.Research Limitation: Very limited position on the board of directors for women in companies causes it to have no effect as a moderating variable. Moreover, this research did not categorize investment efficiency in the overinvestment and underinvestment schemes.